Online music retailing and its implications. - Chong, Chia Suan. (2009)
This paper examines the possible implications online music retail, which makes use of the new encrypted digital downloading technology, for the traditional music retail industry in Singapore. The study draws on preceding work on the impact of electronic commerce on various industries in the US, theories of retail and distribution, reports from newspapers, magazine and electronic publications, and interviews with local industry players.